1995
DOI: 10.1080/15287399509531970
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte‐aniune interaction leads to their accumulation and iron deposition in rat spleen

Abstract: In order to understand the splenic toxicity of aniline in rats, early interaction of aniline with erythrocytes and its subsequent deposition and covalent binding to macromolecules in target (spleen) and nontarget (liver) organs have been studied. Male Sprague-Dawley (SD) rats were given 1 or 3 doses of 1 mmol/kg [14C]aniline hydrochloride (1 dose/d) by gavage and euthanized 24 h after the treatment. Among blood components, maximum radioactivity was found to be associated with red blood cells (RBCs). After 3 do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…Red blood cells are the major site for binding and accumulation of aniline (18,42). Our results on persistence of the 16:0 and 18:1 FAAs in the whole blood as compared to that in liver and pancreas are in agreement with the results of aniline binding with red blood cells.…”
Section: Discussionsupporting
confidence: 94%
“…Red blood cells are the major site for binding and accumulation of aniline (18,42). Our results on persistence of the 16:0 and 18:1 FAAs in the whole blood as compared to that in liver and pancreas are in agreement with the results of aniline binding with red blood cells.…”
Section: Discussionsupporting
confidence: 94%
“…This is similar to findings previously reported with other agents causing MetHb (e.g., Nair et al, 1986;Hamm et al, 1984;Khan et al, 1995aKhan et al, , 1995bKhan et al, , 1998aKhan et al, , 1998bKhan et al, , 2000. In the present study, a statistically significant increase in MetHb levels was observed at 86.2 mg/m 3 air, and hematological as well as splenic changes appear to coincide.…”
Section: Discussionsupporting
confidence: 91%
“…It is beyond the scope of this article to address any aspects of the mechanistic principles of the transformation of p-phenetidine into the active metabolite, the ensuing formation of methemoglobin, and secondary responses occurring in the liver and spleen, which have been reviewed in detail elsewhere (e.g., Kiese, 1974;Khan et al, 1995aKhan et al, , 1995bBus & Popp, 1987;Ferrali et al, 1997).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Atherosclerosis is a progressive (and inflammatory ) disease (Altman 2003; Binder et al 2002; Blake and Ridker 2001; Duewell et al 2010; Dwyer et al 2004; Forrester 2002, 2004; Gieseg et al 2009; Grainger 2007; Hansson 2001, 2005; Himmelfarb et al 2002; Kibel et al 2008; Kunsch and Medford 1999; Libby 2002; Libby et al 2002; Madamanchi et al 2005a, b; Mullenix et al 2005; Nigro et al 2006; Packard and Libby 2008; Paoletti et al 2004; Popa et al 2007; Rader and Daugherty 2008; Ridker et alet al 2004; Ross 1999; Schleicher and Friess 2007; Subramanian and Ferrante 2009; Sullivan 2009; Tan and Lip 2008; Tang et al 2009; Taqueti et al 2006; Tedgui and Mallat 2006; van Leuven et al 2008; van Oostrom et al 2004; Willerson and Ridker 2004; Young et al 2002) characterized by the accumulation of both oxidised lipids and various fibrous elements in arteries, often as plaques (Lusis 2000; Stocker and Keaney 2004). Several lines of evidence point to the involvement of iron in these processes:

Both iron and oxidised lipids (de Valk and Marx 1999; Smith et al 1992) are found in atherosclerotic lesions (Altamura and Muckenthaler 2009; Brewer 2007; Chau 2000; Fernandes de Godoy et al 2007; Gajda et al 2008; Halliwell 2009; Horwitz et al 1998; Kazi et al 2008; Lee et al 1998; McRae et al 2009; Rajendran et al 2007; Ramakrishna et al 2003; Roijers et al 2005; Smith et al 1992; Stadler et al 2004; Stanley et al 2006; Stocker and Keaney 2005; Sullivan 2009; Watt et al 2006; Wolff et al 2004; Yuan and Li 2008)

Iron depletion by dietary or other means delays the formation of such lesions...

…”
Section: Iron Deposition and Disease: Cause Or Effect? The Case Of Atmentioning
confidence: 99%